Analysis of the family’s communication pattern and the benefits of mother school program for building a harmonious family - Firdanianty Pramono (Informasi, 2020)
Positive communication plays an important role in building a harmonious family. The objectives of this research were to: 1) Identify the characteristics of Mother School participants in 3 urban villages in Bogor; 2) Classifying family communication patterns of participants in Mother Schools based on low, moderate, and high categories; and 3) Analyze the benefits of Mother School program. The study was conducted with quantitative and qualitative approaches. The respondents were 84 people from the villages of Ciluar, Ciparigi, and Kedung Halang. Quantitative data were processed descriptively and analyzed using the Anova one way test. The qualitative data were obtained from the writing of participants in Ciluar village as many as 30 people, and then analyzed to find out the benefits of Mother School program. The results showed that the majority (84.62%) of respondents stated strongly agree that family togetherness is everything and 71.79 percent felt very close to their husband and children. By region, the participants of Mother School in Ciparigi village whose family communication was in high category had the highest percentage (60.71%). Maternal education level is considered to be a key factor in family communication in Ciparigi Mother School participants, better than 2 other villages. Qualitative analysis showed that participants feel the benefits of Mother School which can increase knowledge and understanding of how to care their children and build a harmonious family. This research is expected to be input for the Government of Bogor to further improve the quality of family resources.Komunikasi yang positif berperan penting dalam membangun keluarga harmonis. Penelitian ini bertujuan untuk: 1) Mengidentifikasi karakteristik peserta Sekolah Ibu di 3 kelurahan Kota Bogor; 2) Mengelompokkan pola komunikasi keluarga peserta Sekolah Ibu berdasarkan kategori rendah, sedang, dan tinggi; dan 3) Menganalisis manfaat program Sekolah Ibu. Penelitian dilakukan dengan pendekatan kuantitatif dan kualitatif. Responden yang disurvei berjumlah 84 orang berasal dari kelurahan Ciluar, Ciparigi, dan Kedung Halang. Data kuantitatif diolah secara deskriptif dan dianalisis dengan uji one way Anova. Adapun data kualitatif diperoleh dari tulisan peserta di kelurahan Ciluar sebanyak 30 orang, kemudian dianalisis untuk mengetahui manfaat program Sekolah Ibu. Hasil penelitian menunjukkan, sebagian besar (84,62%) responden menyatakan sangat setuju bahwa kebersamaan keluarga adalah segalanya dan 71,79 persen merasa sangat dekat dengan suami dan anak-anaknya. Berdasarkan wilayah, peserta Sekolah Ibu di kelurahan Ciparigi yang komunikasi keluarganya masuk kategori tinggi memiliki persentase terbanyak (60,71%). Tingkat pendidikan ibu diduga merupakan faktor utama komunikasi keluarga peserta Sekolah Ibu di Ciparigi lebih baik dibandingkan 2 kelurahan lain. Analisis kualitatif memperlihatkan, peserta merasakan manfaat Sekolah Ibu yang dapat menambah pengetahuan dan pemahaman tentang cara mengasuh anak dan membangun keluarga harmonis. Penelitian ini diharapkan menjadi masukan bagi Pemerintah Kota Bogor untuk lebih meningkatkan kualitas sumber daya keluarga.